The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1097/sap.0000000000000289
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster in a Free Transverse Rectus Abdominis Myocutaneous Flap After Delayed Breast Reconstruction

Abstract: In concert with advances in surgical reconstruction techniques and improved survival after breast cancer, both the aesthetic and functional outcomes, especially sensory recovery, of breast reconstruction have been addressed. Most studies on sensory recovery in reconstructed breasts have utilized patients’ subjective responses to touch, pain, temperature, and pressure. In contrast, this report describes a case of herpes zoster that developed in a free transverse rectus abdominis myocutaneous flap, which provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Studies that date back to the 1990s have shown that while not all patients recover full sensation, a majority of patients regain some sensation, including light touch, hot/cold recognition, and vibratory sensation, following autologous and free TRAM flaps 2,3 . Additionally, cases of reactivated herpes zoster infection have been reported in patients who received free TRAM and pedicled denervated latissimus dorsi (LD) flaps, providing evidence that spontaneous reinnervation of flaps does occur 4‐6 . More recent studies have found satisfactory progressive recovery of sensation in patients who receive DIEP flaps.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that date back to the 1990s have shown that while not all patients recover full sensation, a majority of patients regain some sensation, including light touch, hot/cold recognition, and vibratory sensation, following autologous and free TRAM flaps 2,3 . Additionally, cases of reactivated herpes zoster infection have been reported in patients who received free TRAM and pedicled denervated latissimus dorsi (LD) flaps, providing evidence that spontaneous reinnervation of flaps does occur 4‐6 . More recent studies have found satisfactory progressive recovery of sensation in patients who receive DIEP flaps.…”
Section: Introductionmentioning
confidence: 99%
“…1 In studies that used herpes zoster lesions as objective proof of reinnervation, lesions occurred after 2 and 6 years after surgery. 6,9 Taken together, these studies have shown that the minimum time to confirm the recovery of sensory nerve is approximately 6 months.…”
mentioning
confidence: 75%
“…In general herpes infections associated with free flaps are rare. After our literature research in pubmed and medline for “flap and herpes zoster”, “flap and zoster” and “flap and herpes”, we were able to identify only four cases after breast reconstruction with rectus abdominis flaps [ 1 2 3 4 ]. The evidence for spontaneous reinervation by herpes zoster infection was recently discussed by Lee and Choi [ 5 ] who observed a herpes zoster infection of a rectus abdominis flap [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this report we would like to describe our experience in a case of blazed up herpes zoster lesions that developed in a denervated pedicled latissimus dorsi flap 2 years after breast reconstruction, proving spontaneous reinervaton of the priorly denervated flap. Only very few cases of herpes zoster infections in transverse abdominis flaps were reported so far [ 1 2 3 4 5 ]. To our knowledge this is the first report of a herpes zoster infection in a latissimus dorsi flap after breast reconstruction.…”
Section: Introductionmentioning
confidence: 99%